Interfacial modification and enhancement of toughening mechanisms in epoxy composites with CNTs grafted on carbon fibers. (6th October 2016) - Mei, Hui; Zhang, Siming; Chen, Hao; Zhou, Huashan; Zhai, Xueyuan; Cheng, Laifei
Abstract: This paper focuses on the reinforcing ability of carbon nanotubes (CNTs) on the interface of the resin-matrix composites and tries to find an effective method to improve its reinforcing ability. CNTs were introduced by electrophoretic deposition, which had little damage to carbon fibers. Tensile tests were conducted to figure out the changes in mechanical properties after depositing CNTs. The results showed that after depositing CNTs on interfaces, tensile strength, failure strain and Young's modulus of the composites increased by 9.86%, 44.01%, and 12.40% respectively. The nitric acid treatment was carried out to activate the reinforcement potential of CNTs, which was verified to increase the tensile strength, failure strain and Young's modulus by 35.7%, 21.7%, and 70.0% respectively. These significant improvements on mechanical properties could be attributed to physical and chemical modification of fiber surfaces, including the change of roughness, functional groups and wettability of fiber surfaces. A better dispersion of CNTs after modification also contributed to the good performance of composites. The bridging mechanisms of CNTs were investigated based on the morphology observation on the interface. The reinforcing effect of CNTs mainly relies on its bridging ability, while two pulling-out modes also play a vital role in reinforcing resin-matrix composites.